Caringscapes: experiences of caring and working - McKie, Linda; Gregory, Susan; Bowlby, Sophie (CRFR, 2004)
There is growing interest in ways in which people combine working with caring, and what can be done to make the balance of work and care more manageable. In this paper, Linda McKie, Susan Gregory and Sophia Bowlby explore experiences of caring and working, arguing that new ways of thinking need to be developed.
Keywords: Care and caring practices; Community care